LEARNING TO LISTEN METACOGNITIVELY - Bouzar, Siham (PEOPLE: International Journal of Social Sciences, 2016)
Learning any language requires the development of receptive skills and productive ones. In other terms, listening, reading, speaking and writing are the major four building blocks. This piece of work focuses mainly on the listening skill as being a highly complicated activity demanding lot of efforts from the learner to construct meaning. Therefore, it is with the perspective to teach EFL/ESL learners how to listen instead of making them listen to learn that this work is achieved.